Silencing the past in Ugandan schools. The role of education in reconciliation processes. (2nd January 2020) - Datzberger, Simone; Donovan, Outi
ABSTRACT: This article assesses how reconciliation in post-conflict Uganda is currently approached in the country's education sector. It highlights that education is in the main equated with economic development thereby side-lining the legacies of past conflicts and social injustices. In the view of Uganda's highly politicised reconciliation process, this may not come as a surprise. Interviewees pointed to a general fear, that addressing past conflicts in official curricula could revive tensions. However, fieldwork further revealed that a sheer absence of reconciliation through the education sector could be dangerous in two ways. First, silencing past conflicts in schools may have a depoliticising effect on a population as a whole. It deprives a society of constructing a social, cultural and national identity that is based on multiple understandings of a conflict. Second, the absence of a social truth based on different narratives of the conflict can in the long-term trigger new forms of structural violence if not conflict or violent unrest.